Understanding the acceptance of medical marijuana among Malaysian adults: a cross-sectional online survey - Rahman, Abu Bakar; Naserrudin, Nurul Athirah; Seman, Zamtira; Mohd Zin, Zaikiah; Dapari, Rahmat; Hassan, Mohd Rohaizat; Ab Rashid, Azman; Muhd Dahaban, Mariatul Umeera; Jahaya, Nadia Hani; Balamurugan, Hema; Krishnan, Manimaran (BMJ Publishing Group, 2026)
Background Global discussions surrounding the medical use of marijuana have gained momentum; yet in Malaysia, cannabis remains strictly prohibited under the Dangerous Drugs Act 1952. Despite its legal status, there is growing public discourse on its potential therapeutic benefits. Understanding public acceptance is critical for informing future health policies and public education efforts. Methods This study used a cross-sectional design, web-based survey among Malaysians aged 18 years and above using convenience and snowball sampling methods. The survey collected data on sociodemographic characteristics, lifestyle factors (eg, smoking and drug use), awareness of medical marijuana and perceived risk. Multivariable logistic regression analysis was performed to identify factors associated with acceptance of medical marijuana decriminalisation. Results Out of 2047 respondents, 88.4% supported medical marijuana decriminalisation based on clinical evidence. Key predictors of acceptance included male gender (adjusted OR (AOR) 1.71; 95%CI 1.29 to 2.26), higher education (Bachelor’s degree AOR 1.56; 95%CI 1.09 to 2.23 and Master’s/PhD AOR 2.04; 95%CI 1.34 to 3.10), self-employment (AOR 1.84; 95%CI 1.22 to 2.77) and private sector employment (AOR 1.40; 95%CI 1.03 to 1.89). Behavioural factors, such as smoking (AOR 1.58; 95%CI 1.10 to 2.27), prior drug use (AOR 1.86; 95%CI 1.30 to 2.67) and low perceived risk (AOR 5.82; 95%CI 3.48 to 9.73), were also significantly associated with acceptance. Conclusions A large proportion of Malaysian adults supported the clinical use of medical marijuana. Acceptance was strongly associated with demographic and behavioural factors, particularly gender, education and perceived risk. These findings may guide the development of targeted public health education and inform future discussions on regulatory approaches in Malaysia.